The influence of TikTok on children's growth, behaviour, digital well-being, social interactions, and cognitive development - Maulida, Ikrima; Nasihin, Muh; Silma, Nazula; Yudistira, Cokorda Gede Putra (Yayasan Mitra Persada Nusantara, 2025)
This research aims to describe the impact of the TikTok social media application on early childhood development. Based on the results of my findings and previous research, it is evident that TikTok has both positive and negative effects on children. The positive impacts include various educational benefits, such as facilitating learning through engaging content, enhancing counting skills, promoting reading, and providing a platform for children to express and develop their creativity. TikTok offers a diverse range of videos that can introduce children to new concepts and ideas, making learning enjoyable and interactive. However, there are several significant negative effects associated with TikTok usage among young children. One major concern is the influence on children's social behaviour, particularly in their interactions with peers and their environment. Excessive use of the app may lead to addiction, causing children to lose track of time and neglect essential daily activities such as eating, bathing, and resting. This overindulgence can result in a decline in physical health and well-being. Additionally, children may show a marked lack of interest in engaging with their peers, opting instead to spend their time on TikTok. This shift in focus can lead to reduced social interaction, making it difficult for children to develop vital social skills. For instance, children may struggle to respond when called or become less aware of their surroundings as they become engrossed in the app. Moreover, frequent TikTok usage can hinder children's ability to communicate effectively with others, as their interactions become predominantly screen-based rather than face-to-face. This phenomenon underscores the need for parental supervision and guidance when children use TikTok. Parents must be vigilant, as many of the contents available on the platform may not be educational or suitable for early childhood, potentially exposing children to inappropriate material. Overall, a balanced approach is essential to maximize the benefits of TikTok while mitigating its adverse effects.